Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1007/s00167-020-06319-4
|View full text |Cite
|
Sign up to set email alerts
|

Local curvature mismatch may worsen the midterm functional outcomes of osteochondral allograft transplantation

Abstract: PurposeThis study aimed to determine the magnitude of local curvature matching in the sagittal plane between an implanted graft and the condylar region receiving the graft and to analyze its effect on clinical outcomes in patients undergoing osteochondral allograft transplantation (OCA). MethodsPatients who underwent knee OCA between 2016 and 2019 without circumferential step‐off and were matched with a donor in accordance with the conventional matching process were included. The magnitude of donor‐host local … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Many studies have shown the importance of matching the AC surface of the knee joint with the natural topographic anatomy during OCA transplantation. [31][32][33] The failure to match these components may negatively affect clinical outcomes [31,34] and subregional transplantation may be the solution. There was no signi cant difference in biomechanical properties between LP and MP, or between LTP and MTP; therefore, no more detailed division was required.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown the importance of matching the AC surface of the knee joint with the natural topographic anatomy during OCA transplantation. [31][32][33] The failure to match these components may negatively affect clinical outcomes [31,34] and subregional transplantation may be the solution. There was no signi cant difference in biomechanical properties between LP and MP, or between LTP and MTP; therefore, no more detailed division was required.…”
Section: Discussionmentioning
confidence: 99%
“…Gursoy et al 9 indirectly investigated the effect of RC mismatch by measuring local curvature mismatch between the donor and host in the setting of femoral condyle OCA transplant. Large relative graft convexity demonstrated a negative effect on clinical outcomes in that retrospective comparative study.…”
Section: Discussionmentioning
confidence: 99%
“…Mismatched graft curvature can produce at least a moderate increase in peak contact stresses about grafted site and has been shown to be associated with worse clinical outcomes. 24,36…”
Section: Discussionmentioning
confidence: 99%
“…When OAT donor grafts do not match the curvature of the recipient region, this can lead to significantly poorer clinical outcomes. 24…”
Section: Introductionmentioning
confidence: 99%